On the automorphism groups of relatively free groups of infinite rank: a survey - Roman’kov, V.A. (Ye.A.Buketov Karaganda State University Publishing house, 2018)
The paper is intended to be a survey on some topics within the framework of automorphisms of a relatively free groups of infinite rank. We discuss such properties as tameness, primitivity, small index, Bergman property, and so on.
Шексіз рангті еркін группаларға қатысты автоморфизмдер группалары жайында:шолу
О группах автоморфизмов относительно свободных групп бесконечного ранга: обзор
Keywords: variety of groups; relatively free group; countably infinite rank; automorphism group; tame automorphism; small index property; cofinality; Bergman property